Effect of human menopausal gonadotropin on reproductive efficiency of Awassi ewes outside the reproductive season (Damascus University Journal of agriculture sciences, 2023)
This study aimed to evaluate pregnancy rates in Awassi ewes, after substitution of hMG for eCG with progestagens during the non-breeding season. 20 multiparous Awassi ewes were randomly allocated into two equal treatment groups. Vaginal sponges have been inserted for 14 days to all of treatment groups. along with intravaginal sponges withdrawal, Follicular development was induced in the control group with 750 IU eCG and in the second group with 25 IU hMG and ovulation was induced 52h after hMG administration with 1000 IU hCG. All ewes were artificially inseminated at fixed time after 24h of hCG administration with fresh diluted semen collected using an electroejaculator just before insemination time. An ultrasound scanner equipped with a linear transducer probe with a frequency of 7.5 MHz was used to monitor ovarian follicles for three consecutive days, starting at gonadotropin administration, and to diagnose pregnancy at 35 d post A.I. Statistical differences (P
Keywords: hMG; eCG; Intravaginal Sponges; Awassi Ewes